Old peoples' well being in a total institution and the imperative of new policy directive (2016)
In contemporary times, African as well as Nigerian societies have experienced changes due to urbanization, globalization, and industrialization. This has resulted in a weakening of the hitherto existing bonds, norms, values and culture in the family structure with the attendant consequences of neglecting the elderly. While studies have focused on the factors militating against adequate care for the elderly, psychological well being of the elderly as well as their unmet needs, dearth of information exist on the social well-being of the elderly who are under care and support in the institution such as the Yaba old people's home. This study was conducted against this background with the social exchange theory and Health Belief Model as its theoretical frameworks. The study was purely qualitative using in- depth interview with 44 resident aged people, 3 key informant interviews with staff of the institution and nonparticipant observation as the methods of data collection. Over half (59.0%) of the respondents are female while about a quarter of the respondents (23.0%) most of whom were females, had no education. Furthermore, while 91.0% were between the ages of 71-90years, 98.0%, of the respondents were widowed prior to their admission into the homes. Findings revealed that the elderly experienced dissatisfaction with the food, access to medical attention and condition of living in the institution. This was revealed to be because they lacked choice as to what to eat, where to stay, who to stay with and when to receive medical attention. Lack of adequate funding from government, inconsistent payment from relations of the elderly, and limited supplies of resources were reported as the challenges faced by the institutions which affected the care of the elderly in the home. Adequate funding, consistent payment and increased support from government, clients relations and other necessary stakeholders respectively are recommended in order to ameliorate the conditions of the aged in Nigeria in particular and African in general.